KEMAMPUAN KOMUNIKASI DAN BERPIKIR LOGIS MATEMATIKSERTA KEMANDIRIAN BELAJAR - Hidayat Wahyu; Utari Sumarmo (Universitas Khairun, 2013)
This paper reports the findings from a postest experimental control group design conducted in 2011 to investigate students’ mathematical communication and logical thinking abilities and self regulated learning. The study involves 76 students of grade-11 from a senior high school in Cimahi. The study employs three kinds of instrument namely mathematical communication and mathematical logical thinking test and self regulated learning scale. The study found that there was no difference grades of mathematical communication and mathematical logical thinking abilities and self regulated learningbetween students taught by problem based learning and think-talk-write strategy (PBL-TTW) and students taught by conventional teaching. Students’ mathematical communication and mathematical logical thinking abilies were classified as medium, and self regulated learning of student were classified as fairly good. The other findings were there were not association among mathematical abilities and self regulated learning.